Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan - Alfian Nurrohmat; Rini Lestari (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Job satisfaction can improve the performance of employees of a company. The phenomenon that occurs at PT Kahatex in Bandung Regency shows that poor job satisfaction can result in employees often going in and out and not surviving in the company for a long period of time. In addition, the implementation of activities with main tasks and functions that are not in accordance with the expectations of the organization is the result of poor employee performance. This investigation means to have the option to clarify work fulfillment, representative execution and the greatness of the impact of occupation fulfillment on worker execution at PT Kahatex in Bandung Regency. The sample in this study was PT Kahatex in Bandung Regency, namely all employees at PT Kahatex in Bandung Regency. The information assortment method utilized is as a survey with 30 respondents. The example determination method in this examination is a non-probability sampling technique with a convenience sampling technique. Hypothesis testing used is simple linear regression. The results showed that job satisfaction and employee performance at PT Kahatex in Bandung Regency were included in the